Home and migrant identity in dialogical life stories of Moroccan and Turkish Dutch - Stock, Femke J. (Muslim Minorities, 2017)
In Home and Migrant Identity in Dialogical Life Stories of Moroccan and Turkish Dutch , Femke J. Stock explores the multivoiced life stories of Dutch adults of Moroccan and Turkish descent. Focusing on stories about 'home', this book deals with social relationships and being oneself, countries and houses, discrimination and Islamophobia, family and religion, and how these feature in personal narratives. Through microanalysis of case study material using Dialogical Self Theory, this book formulates and substantiates clear insights into descendants of migrants' roots and routes, their sense of home, and their ambivalent processes of (dis)identification and belonging. Showing how religion plays a relatively marginal role in personal narratives, it provides an antidote to the widespread tendency to address and study Muslims almost exclusively in terms of their religious identity.